Effective communication at the point of multiple sclerosis diagnosis. (April 2014) - Solari, Alessandra
As a consequence of the current shortened diagnostic workup, people with multiple sclerosis (PwMS) are rapidly confronted with a disease of uncertain prognosis that requires complex treatment decisions. This paper reviews studies that have assessed the experiences of PwMS in the peri-diagnostic period and have evaluated the efficacy of interventions providing information at this critical moment. The studies found that the emotional burden on PwMS at diagnosis was high, and emphasised the need for careful monitoring and management of mood symptoms (chiefly anxiety). Information provision did not affect anxiety symptoms but improved patients' knowledge of their condition, the achievement of 'informed choice', and satisfaction with the diagnosis communication. It is vital to develop and implement information and decision aids for PwMS, but this is resource intensive, and international collaboration may be a way forward. The use of patient self-assessed outcome measures that appraise the quality of diagnosis communication is also important to allow health services to understand and meet the needs and preferences of PwMS.